The Impact of Smartphone Addiction and Family Support on Maternal Caregiving Ability for Children with Preoperative Anxiety - Pratama, Edy Surya; Sismulyanto (Journal of Health Science and Prevention, 2026)
Support for mothers in caring for children experiencing anxiety during the preoperative phase is very important. Smartphones and family become sources of support for mothers in caring for children with anxiety during the preoperative phase. This study aims to analyze the influence of smartphone addiction and family support on maternal care ability in children experiencing anxiety in the preoperative phase. This research uses a cross-sectional design, where the population in this study is mothers with children experiencing anxiety in the preoperative phase. The sample in this study consisted of 132 mothers of children aged 3-6 years who were hospitalized and awaiting surgery. Participants were purposively selected from two hospitals in Mataram City, Indonesia. Data were collected using the Smartphone Addiction Scale-Short Version (SAS-SV), Family Support Scale (FSS), maternal care questionnaire, and the modified Yale Preoperative Anxiety Scale (m-YPAS). Multiple linear regression analysis was performed in SPSS version 25.0 to assess the influence of the variables. The results of the analysis showed that both smartphone addiction and family support are significant predictors of maternal caregiving ability. Partially, smartphone addiction has a weak negative effect on maternal caregiving ability (β = -0.038, p = 0.047), whereas family support has a strong positive effect (β = 0.974, p < 0.001). This study indicates that interventions that involve and empower the family as a support system for mothers can improve maternal caregiving ability.